More schooling, more children: Compulsory schooling reforms and fertility in Europe - Margherita Fort; Nicole Schneeweis; Rudolf Winter-Ebmer (Institute for Advanced Studies (IHS), 2011)
We study the relationship between education and fertility, exploiting compulsory schooling reforms in Europe as source of exogenous variation in education. Using data from 8 European countries, we assess the causal effect of education on the number of biological kids and the incidence of childlessness. We find that more education causes a substantial decrease in childlessness and an increase in the average number of children per woman. Our findings are robust to a number of falsification checks and we can provide complementary empirical evidence on the mechanisms leading to these surprising results.
Keywords: I2; J13; 330; instrumental variables; education; fertility